Clear-sky solar radiation changes over arid and semi-arid areas in China and their determining factors during 2001–2015. (15th February 2020) - Yu, Lan; Zhang, Ming; Wang, Lunche; Qin, Wenmin; Lu, Yunbo; Li, Junli
Abstract: In the study, we investigated the clear-sky solar radiation at the surface and their determining factors over the arid and semi-arid (ASA) areas in China using the simulations by Mesoscale Atmospheric Global Irradiance Code (MAGIC) radiation code with satellite remote sensing aerosol data and reanalysis data as input. The coefficient of determination (R 2 ) between ground-based measurements and simulations was 0.959, and the average relative error was 6.33%. Stations with an average relative error of less than 10% accounted for 100%, confirming the reliability of simulations. The distribution of clear-sky solar radiation showed low values in regions with high latitudes and low altitudes, and high ones in regions with low latitudes and high altitudes. The monthly average of water vapour radiative effects (WVRE) was higher than the monthly average of aerosol direct radiative effects (ADRE) for each month. WVRE were even more than six times that of ADRE in July, August, September, indicating that water vapour has stronger weakening of clear-sky solar radiation than aerosols. The annual trend indicated increases in clear-sky solar radiation in most part of ASA areas. Central Inner Mongolia (0.389 W m −2 year −1 ) has the significant increase. There was an interesting finding that the area where the clear-sky solar radiation decreased/increased has a good match with the area where ADRE enhanced/weakened. The R 2 between clear-sky solar radiation trend and ADRE trend was 0.957, indicating that the ADRE trends were the determining factor of the clear-sky solar radiation trends. Central Inner Mongolia (0.345 Wm -2 year −1 ) has the significant weakening of ADRE. Graphical abstract: Variation trends of clear-sky solar radiation in the ASA areas from 2001 to 2015. Regions with significant trends (at 95% confidence level) are dotted. Image 1 Highlights: Clear-sky solar radiation changes over ASA areas were analyzed in China. Attenuation of clear-sky radiation due to water vapour was stronger than aerosols. Central Inner Mongolia showed significant increasing clear-sky solar radiation. The trends of clear-sky solar radiation was mainly determined by the trends of ADRE.